2019
DOI: 10.1002/ijc.32311
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CEP128 promotes bladder cancer progression by regulating Mir‐145‐5p/Myd88 via MAPK signaling pathway

Abstract: The present experiment was designed for exploring the regulatory mechanism of circ‐CEP128/miR‐145‐5p/MYD88 axis in bladder cancer. MiRNAs and circRNAs expression data were derived from Gene Expression Omnibus database with bladder tumor tissues and paracarcinoma tissue samples. Differentially expressed genes in tumor were analyzed via R software. Interaction network of differently expressed miRNAs and differently expressed mRNA was established by means of Cytoscape software. CircCEP128 and miR‐145‐5p expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 31 publications
(52 reference statements)
1
54
0
Order By: Relevance
“…Hence, researches of circular RNAs are divided into 2 parts, one is to identify its carcinogenic role, the other is to prove its application as a biomarker [5]. Serving as an oncogene or tumor suppressor gene, in bladder cancer, ciRS-7 is found to suppress bladder cancer growth by elevating p21 [6]; hypoxia elevates circELP3 to promote bladder cancer progression and drug resistance [7]; circular RNA CEP128 promotes bladder cancer cell propagation and migration via regulating MAPK signaling [8]; and circHIPK3 decreases lung metastasis through suppressing heparanase expression [9]. Besides, as a biomarker [10], up-regulated circPRMT5 in the exosomes from serum and urine positively correlates with metastasis of bladder cancer patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researches of circular RNAs are divided into 2 parts, one is to identify its carcinogenic role, the other is to prove its application as a biomarker [5]. Serving as an oncogene or tumor suppressor gene, in bladder cancer, ciRS-7 is found to suppress bladder cancer growth by elevating p21 [6]; hypoxia elevates circELP3 to promote bladder cancer progression and drug resistance [7]; circular RNA CEP128 promotes bladder cancer cell propagation and migration via regulating MAPK signaling [8]; and circHIPK3 decreases lung metastasis through suppressing heparanase expression [9]. Besides, as a biomarker [10], up-regulated circPRMT5 in the exosomes from serum and urine positively correlates with metastasis of bladder cancer patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…To further explore the roles of these all DE‐circRNAs on downstream genes, GO enrichment, KEGG pathway analysis were also conducted to evaluate the predicted critical genes of them. As shown in Figure 3B,C, several cancer‐related pathways, such as pathways in cancer, cell cycle, PI3K‐Akt signaling pathway, MAPK signaling pathway, cellular senescence, were significantly enriched and promote various cancer cell growth, invasion, and metastasis 56,64,65 . Furthermore, protein‐protein interaction (PPI) network and module analysis of 94 DE‐genes predicted by screened eight DE circRNAs are delineated in Figure 6.…”
Section: Discussionmentioning
confidence: 96%
“…Mechanistically, circRNA can sponge miRNA to participate in the progression of GC [11,13]. Previous studies showed that circZNF609, circ_0058063, and circCEP128 sponge miR-145-5p to promote cancer progression [26][27][28]. Likewise, we identified that circDUSP16 was co-localized with miR-145-5p in the cytoplasm of GC cells, and displayed a negative correlation with miR-145-5p expression in GC tissue samples.…”
Section: Discussionmentioning
confidence: 58%